Management of traumatic brain injury in the non‐neurosurgical intensive care unit: a narrative review of current evidence. (12th January 2023) - Wiles, M. D.; Braganza, M.; Edwards, H.; Krause, E.; Jackson, J.; Tait, F.
Summary: Each year, approximately 70 million people suffer traumatic brain injury, which has a significant physical, psychosocial and economic impact for patients and their families. It is recommended in the UK that all patients with traumatic brain injury and a Glasgow coma scale ≤ 8 should be transferred to a neurosurgical centre. However, many patients, especially those in whom neurosurgery is not required, are not treated in, nor transferred to, a neurosurgical centre. This review aims to provide clinicians who work in non‐neurosurgical centres with a summary of contemporary studies relevant to the critical care management of patients with traumatic brain injury. A targeted literature review was undertaken that included guidelines, systematic reviews, meta‐analyses, clinical trials and randomised controlled trials (published in English between 1 January 2017 and 1 July 2022). Studies involving key clinical management strategies published before this time, but which have not been updated or repeated, were also eligible for inclusion. Analysis of the topics identified during the review was then summarised. These included: fundamental critical care management approaches (including ventilation strategies, fluid management, seizure control and osmotherapy); use of processed electroencephalogram monitoring; non‐invasive assessment of intracranial pressure; prognostication; and rehabilitation techniques. Through this process, we have formulated practical recommendations to guide clinical practice in non‐specialist centres.